Incidence of Contrast-Induced Nephropathy And Its Contribution Factors After Cardiac Catheterization in Type II Diabetic Patients: Contrast-Induced Nephropathy - Ramzan, Muhammad; Saeed, Hadi Yousuf; Bhutta, Muhammad Masood Iqbal; Ali, Farman (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the incidence of contrast-induced nephropathy (CIN) and its contributing factors after cardiac catheterization in type II diabetic patients. Study Design: Cross sectional study. Place and Duration of Study: Choudhary Pervaiz Ellahi Institute of Cardiology (CPEIC), Multan for six months, from Aug 2016 to Mar 2017. Material and Methods: This cross sectional study was conducted and completed in the department of cardiology Choudhary Pervaiz Ellahi Institute of Cardiology (CPEIC), Multan for six months (August 2016 to March 2017). Before start of the study ethical approval was obtained from hospital ethical board/committee; informed consent was taken from patients and their attendants after complete information and they were also ensured about their confidentiality. All collected data was aligned and entered in a computer software SPSS version 23.1 and data was analyzed. Mean ± SD values were calculated and presented for quantitative data variables like age, similarly frequency (percentages) were calculated and presented for qualitative variable data like gender. After stratification of data, student chi square test was used to see effect modification. A p-value ≤0.05 was considered as significant. Results: A total number of 255 patients were included in the study. All patients were admitted for cardiac catheterization. Participants of the study were divided into two groups on the basis of CIN presence. Group A consisted of 210 patients who didn’t develop contrast-induced nephropathy (CIN) after catheterization of coronary artery. Group B consisted of 45 patients of CIN after catheterization of coronary artery. It was found that incidence of CIN in diabetic patients with micro-albuminuria was 17.64% (n=45). Conclusion: Observation of our study found that diabetic patients either with normal baseline creatinine are at an increased risk of developing CIN after angiography of coronary artery.